The EBITDA disclosed by companies listed on Brazil stock exchange (B3): locations, types, and occurrence count - Shaiane Pisa Kistner; Orion Augusto Platt Neto (Revista Ambiente Contábil)
Purpose: To identify the types of EBITDA and locations disclosed by publicly traded companies in Brazil.